MILK AGGRAVATES ASTHMA – THE TRUTH OR THE PERCEPTION - Khan, Muhammad Khalid Azam; Naz, Shazia; Khattak, Abdul Latif; Kashif, Nauman; Bukhari, Syed Karamat Hussain Shah; Khan, Asif Ullah (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess the notion that milk can cause or aggravate asthma and break this myth.Study Design: A cross sectional study.Place and Duration of Study: Medicine department, Combined Military Hospital Lahore, from Jan 2019 to Dec2020.Methodology: A survey was conducted whereby known asthmatics were questioned about their opinion weather milk aggravates their asthma. Those who confirmed their positive response were exposed to milk and some liquid resembling milk, and their Lung functions were tested after each drink. The 42 patients who considered milk as the primary aggravator were called for the study for spirometryResults: A total of 600 people from the general population were surveyed. Two hundred and six (34.3%) of them were illiterate, 394 (65.6%) were educated from middle to graduates. In the first milk/milk encounter, the combined dyspnea scale showed increase of 50.3% and improvement of 0.008% in FEVI/FVC. In the second substitute/milk encounter, the dyspnea score showed an increase of 61.8% and an increase of 0.90% in FEVI/FVC. In the third milk/substitute encounter the dyspnea score showed a decrease of 22.9% and the FEVI/FVC decreases by 5.5%. In the 4th substitute/substitute encounter, dyspnea scores decreased by 8.4% while the pre and postencounter FEVI/ FVC scores were 2726 and 2711 with 0.55% decrease with insignificant p-value >0.05.Conclusion: Drinking milk or milk substitute has negligible effect on the spirometric parameters.